Unemployment Perspectives and Solutions - Liu, Yang (IntechOpen, 2017)
This book is a collection of original works by authors from all over the world on aspects of unemployment and job issues, seen from various angles and based on their recent research. It sheds light on fresh ideas on unemployment, such as the intergenerational approach and unemployment normalization, and offers solutions from diverse areas such as social economy development and policy-making. Practical issues regarding job creation and labor mobility are also covered. The book aims to provide not only a better understanding of the nature and extent of unemployment in various parts of the world but also solutions in diverse contexts.